Investigation of the crack healing performance in mortar using microbially induced calcium carbonate precipitation (MICP) method - Jongvivatsakul, Pitcha; Janprasit, Karn; Nuaklong, Peem; Pungrasmi, Wiboonluk; Likitlersuang, Suched (Construction & building materials, 2019)
•Dropping method of MICP was introduced for crack-healing in mortar.•MICP agent was dropped on cracked mortar to improve strength and water tightness.•CaCO3 biomineralization can reduce crack area up to 85% after treatment.•Compressive strength of treated mortar was 43% higher than that of cracked sample.•Water tightness of treated mortar was comparable to that of mortar without crack. This study presents the feasibility of using bacterial cells to repair of the existing cracks within the cement mortar. Bacillus sphaericus (LMG 22257) has been used to produce microbially induced calcium carbonate precipitation (MICP) for crack closing. The healing agent were externally applied to the cracked mortar specimens by dropping the bacteria and urea solutions daily. After 20 days of treatment, the MICP-treated sample showed 43% higher compressive strength than that of cracked sample. In addition, it is comparable in terms of water tightness to control mortar made without artificial crack.